POTENSI KAYU PERTUKANGAN DAN BAHAN SERPIH DI AREAL BEKAS TEBANGAN HUTAN RAWA (Studi Kasus Pemanfaatan Kayu untuk Penyiapan Lahan HPHTI, Riau) - Endom, Wesman; Nitibaskara, Tb. Unu (Jurnal Nusa Sylva, 2015)
The potency of Log Over Forest (LOF) of swamp forests concession had been supplied woods for raw materials of pulp and paper industries in Riau. It potency is classified into Group Diameter (KD). Fist, the average of KD less than 30 cm is about 41.05 m3/ha. It potency is used as raw material for pulp and paper industry which is familiar called as ‘Bahan Baku Serpih’ (BBS). Second, it is KD 30-49 cm which has potency about 32.84 m3/ha. Mostly it is used for carpeting industries. Third, it is KD bigger than 50 cm which has potency about 39.16 m3/ha include of decaying logs with holes. 20% of it is used for BBS and 80% others for carpeting industries. The total potency is about 112.76 m3/ha.